PENTINGNYA LINGKUNGAN KELUARGA DALAM PENGEMBANGAN KEWIRAUSAHAAN ISLAM - Khairul Hasanah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
For Muslims, entrepreneurship is a part of the process of seeking Allah SWT's pleasure in order to have good fortune in this life and the next. The literature review in this research aims to learn more about the function of family in character development and entrepreneurial interest. To thrive in entrepreneurship, a person's individuality and distinct motives are required. One's family may have an impact on all of one's business ambitions. This first educational setting can also give entrepreneurship information and abilities. It would be fantastic if the parents received it as well.